2017
DOI: 10.1002/14651858.cd005364.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Topical anaesthetics for pain control during repair of dermal laceration

Abstract: , Baraa.Tayeb@tu s.edu. Editorial group: Cochrane Anaesthesia Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 2, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Another study of adults with facial lacerations found addition of topical eutectic mixture of local anesthetics to routine care decreased pain and improved patient satisfaction scores [21]. A Cochrane review of 25 randomized controlled trials totaling 3,278 patients compared topical versus infiltrated anesthetics and found that topical anesthetics had no complications and provided effective pain control, with some individual studies suggesting similar efficacy to local anesthesia [22]. Topical anesthetics offer many advantages and may be underutilized.…”
Section: Sedation and Analgesiamentioning
confidence: 99%
“…Another study of adults with facial lacerations found addition of topical eutectic mixture of local anesthetics to routine care decreased pain and improved patient satisfaction scores [21]. A Cochrane review of 25 randomized controlled trials totaling 3,278 patients compared topical versus infiltrated anesthetics and found that topical anesthetics had no complications and provided effective pain control, with some individual studies suggesting similar efficacy to local anesthesia [22]. Topical anesthetics offer many advantages and may be underutilized.…”
Section: Sedation and Analgesiamentioning
confidence: 99%
“…A common minor surgical procedure in the discipline of general practice is the dermal laceration repair with sutures. Alleviation of the pain caused by this procedure is conventionally achieved through local anaesthetic infiltration, that is, by injection (De Lemos, 2022;Tayeb et al, 2017). However, the injection, itself, may cause significant pain, even if topical anaesthetics are applied in advance to numb the area temporarily.…”
Section: Minor Surgical Proceduresmentioning
confidence: 99%
“…However, the injection, itself, may cause significant pain, even if topical anaesthetics are applied in advance to numb the area temporarily. Accordingly, many patients, especially children, fear injections (Tayeb et al, 2017). This not only precipitates mental distress but acute physical stress too, such as, the acute stress response, otherwise known as the fight-or-flight response (Cannon, 1915), which is a survival or adaptive physiological reaction that affects the regulation of all the systems of the body, including the cardiovascular, respiratory, endocrine, gastrointestinal, nervous, muscular, and reproductive systems (Chu et al, 2022).…”
Section: Minor Surgical Proceduresmentioning
confidence: 99%
“…However the process of injecting this medication into the skin and subsequent infiltration of tissue can cause discomfort and anxiety in patients, especially in children and those with a needle phobia. Therefore the use of topical agents, for example gels or solutions, to deliver local anaesthetic has been proposed as an alternative (Tayeb et al, 2018). These medications need to be managed carefully as high doses can lead to adverse side effects including hypotension, cardiac arrhythmias, double vision and seizures (Stoelting, 1999).…”
Section: Introductionmentioning
confidence: 99%